Meeting social needs and loneliness in a time of social distancing under COVID-19: A comparison among young, middle, and older adults. Issue 1 (19th May 2021) - Teater, Barbra; Chonody, Jill M.; Hannan, Katrina
ABSTRACT: Loneliness has a significant impact on the health and wellbeing of people. The COVID-19 pandemic has demanded individuals to socially distance, which has implications for loneliness and social isolation. This cross-sectional study explored the ways in which people in the United States ( N = 412) are meeting their social needs in a time of social distancing, how these activities relate to levels of loneliness, and any differences among young, middle-aged, and older adults. Results indicated higher levels of loneliness and social isolation for the entire sample and across the three age groups from pre- to during COVID-19 with younger adults experiencing higher levels of emotional loneliness during COVID-19. The extent to which the activities were related to loneliness was only found among the young adults and older adults where outdoor meet-ups, talking on the phone, and texting was associated with lower levels of loneliness among the young adults, and engaging in social media and talking on the phone was associated with lower levels of loneliness among the older adults. The findings support social work and public health recommendations for addressing loneliness during times of social distancing under the COVID-19 pandemic and future public health crises.